Ginsenoside Rg2 alleviates myocardial fibrosis by regulating TGF-β1/Smad signalling pathway - Quanwei Wang; Wenwen Fu; Xiaofeng Yu; Huali Xu; Dayun Sui; Yeling Wang (Taylor & Francis Group, 2021)
Context Panax ginseng C.A. Meyer (Araliaceae) has cardioprotective effects. Ginsenosides are responsible for most of the pharmacological activities of ginseng. Objective This study investigates the effect of ginsenoside Rg2 on myocardial fibrosis in myocardial ischaemia rats. Materials and methods Male Wistar rats were divided into control, isoproterenol, ginsenoside Rg2 (5, 20 mg/kg) groups (n = 8). The rats were subcutaneously injected with isoproterenol (5 mg/kg) or normal saline (control group) once daily for 7 days. The animals were intragastrically treated with ginsenoside Rg2 or 0.5% CMC-Na (control and isoproterenol groups) daily for 28 days. At day 28, cardiac function, myocardial fibrosis, and TGF-β1/Smad signalling pathway were evaluated. Results Compared with myocardial ischaemic rats, ginsenoside Rg2 at doses of 5, 20 mg/kg abated partially the augment of LVEDP (8.9 ± 1.3 vs. 7.5 ± 0.7, 7.2 ± 1.0 mmHg) and the decreases of the LVSP (96.75 ± 13.2 vs. 118.3 ± 19.4, 124.3 ± 21.3 mmHg), the + dp/dt (2142.8 ± 309.3 vs. 2598.6 ± 404.0, 2661.5 ± 445.2 mmHg/s), and the -dp/dt (1996.3 ± 306.3 vs. 2476.6 ± 289.7, 2509.6 ± 353.1 mmHg/s). Ginsenoside Rg2 (9.2 ± 0.9%, 8.5 ± 0.8%) alleviated myocardial fibrosis when compared with the isoproterenol group (10.1 ± 1.0%), which was accompanied by suppressed TGF-β1/Smad signalling in heart tissues. Conclusions Ginsenosides from ginseng possess the property of alleviating myocardial fibrosis, improving cardiac function after myocardial ischaemia. Ginsenosides may be promising agents for improving the outcomes of patients with myocardial ischaemia.